Atlas of nascent RNA transcripts reveals tissue-specific enhancer to gene linkages - Rutendo F. Sigauke; Lynn Sanford; Zachary L. Maas; Taylor Jones; Jacob T. Stanley; Hope A. Townsend; Mary A. Allen; Robin D. Dowell (BMC Genomics)
Abstract Gene transcription is controlled and modulated by regulatory regions, including enhancers and promoters. These regions are abundant in non-coding bidirectional transcription that results in generally unstable RNA. Using nascent RNA transcription data across hundreds of human samples, we identified over 800,000 regions containing bidirectional transcription. We then identify tissue specific, highly correlated transcription between bidirectional and gene regions. The identified correlated pairs, a bidirectional region and a gene, are enriched for disease associated SNPs and often supported by independent 3D data. We present these resources as a database called DBNascent ( https://nascent.colorado.edu/ ) which serves as a resource for future studies into gene regulation, enhancer associated RNAs, and transcription factors.